Sustainable Leadership Through Soul Care : Internal Balance Management Strategis to Prevent Clergy Burnout - Deni Leyden Waljufri (International Forum of Researchers and Lecturers, 2025)
This article aims to analyze and formulate Soul Care as a leadership management strategy to address the crisis of extreme fatigue (burnout) among church leaders, in order to achieve Sustainable Leadership. The burnout phenomenon is reviewed as a crisis of self-management and morals resulting from a misinterpretation of Servant Leadership that demands unlimited sacrifice. This research uses a qualitative literature review method with a Practical Theology approach and interdisciplinary analysis (Theology, Psychology, Management). Findings indicate that Soul Care is not a choice, but a normative command rooted in Sabbath Theology (the command for rest as a divine instruction) and exemplified by Jesus Christ (withdrawing for prayer and rest). Soul Care is practically implemented through disciplined and holistic Self-Boundary Management, encompassing temporal, physical, and emotional dimensions, which serves as a preventive strategy against fatigue. The synthesis of these findings yields the Sustainable Leadership model, which emphasizes that a leader's inner balance and self-wholeness are mandatory foundations for Ethical Integrity and successful long-term ministry.